2019
DOI: 10.3390/metabo10010018
|View full text |Cite
|
Sign up to set email alerts
|

On the Inverse Correlation of Protein and Oil: Examining the Effects of Altered Central Carbon Metabolism on Seed Composition Using Soybean Fast Neutron Mutants

Abstract: Protein and oil levels measured at maturity are inversely correlated across soybean lines; however, carbon is in limited supply during maturation resulting in tradeoffs for the production of other reserves including oligosaccharides. During the late stages of seed development, the allocation of carbon for storage reserves changes. Lipid and protein levels decline while concentrations of indigestible raffinose family oligosaccharides (RFOs) increase, leading to a decreased crop value. Since the maternal source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 61 publications
(111 reference statements)
1
29
0
Order By: Relevance
“…Unlabeled and 64 h labeled Camelina tissue separated into embryo axis and cotyledon, were extracted using a phase separation method, previously described with slight modifications [ 50 ]. Briefly, 700 µL of 3:1 ( v / v ), chloroform: methanol solution was added to dried lyophilized tissue along with 10 µL of EquiSPLASH ® (Avanti polar lipids, Birmingham, AL, USA) as labeled internal standard mix.…”
Section: Methodsmentioning
confidence: 99%
“…Unlabeled and 64 h labeled Camelina tissue separated into embryo axis and cotyledon, were extracted using a phase separation method, previously described with slight modifications [ 50 ]. Briefly, 700 µL of 3:1 ( v / v ), chloroform: methanol solution was added to dried lyophilized tissue along with 10 µL of EquiSPLASH ® (Avanti polar lipids, Birmingham, AL, USA) as labeled internal standard mix.…”
Section: Methodsmentioning
confidence: 99%
“…Pearson correlation analysis was also performed for each location ( Figure 5 ). Despite the well-known negative correlation between oil and protein [ 13 ] that was observed in both locations (r ≤ −0.51, p < 0.05), new correlations were identified. In agreement with PC3 loading coefficients ( Figure S4, Table S2 ), although maltose content is low in comparison to the other sugars ( Table S3 ), it showed a significant positive correlation with oil in both locations (r ≥ 0.42, p < 0.05) and a negative correlation with protein that was significant in AR (r ≤ −0.48, p < 0.05), with the same tendency in NC (r ≤ −0.4, p < 0.1, Figure 5 ).…”
Section: Resultsmentioning
confidence: 84%
“…It has been hypothesized that carbon derived from the turnover of lipids and proteins contributes to the synthesis of RFOs. A recent study using fast neutron-mutagenized soybean populations with deletions in central carbon metabolic genes showed that a delayed switch in carbon allocation towards RFO biosynthesis resulted in extended lipid accumulation without compromising protein content [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ammonia derived from nitrogen uptake by maternal vegetative tissues is the primary source for supply the nitrogen predominantly as amino acid such as glutamine and asparagine to the seeds (Ohyama et al 2017). In addition, amino acids participate in the synthesis of storage proteins and thereby contributing the carbon remobilization through proteolysis activity during the late seed developmental stages (Galili et al 2014;Kambhampati et al 2020). Here, 64 proteases showed increased abundance in Saedanbaek that might be having a crucial role in the remobilization of endogenous nitrogenous products such as amino acid or proteins to storage proteins (Gallardo et al 2006(Gallardo et al , 2007.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, during seed maturation stages, 10 to 15% of lipids are converted to raffinose family oligosaccharides (RFOs) when the supply of exogenous resources from maternal plants are limited (Kambhampati et al 2020). These RFOs aere produced by carbon remobilization from lipid along with sucrose during the development of seeds (Kambhampati et al 2020).…”
Section: Discussionmentioning
confidence: 99%